The presence of the discipline of orofacial pain and temporomandibular disorders in the colleges of dentistry in northeast Brazil (Research, Society and Development, 2020)
Problems related to orofacial pain and temporomandibular disorders affect psychosocial functioning and people’s life quality. Objective: To identify the discipline of orofacial pain and temporomandibular disorder in the curriculum of universities in the Northeast of Brazil. Methods: Research that deals with a cross-sectional study carried out in two stages: initially the research was carried out by institutions accredited by the Ministry of Education, excluding participants who presented the course as not started, interrupted or extinguished; afterward, a search was made for the curricular matrix of each institution, recording the presence of discipline, subject hours, theoretical or theoretical-practical teaching, total undergraduate hours and administrative category (public or private). Institutions that did not have a curriculum in their e-mail addresses were excluded. Results: Of the 101 selected institutions, 49 presented the discipline of orofacial pain and temporomandibular disorder in their grade, 83% of which were private administration. The total workload of the Dentistry course corresponded, on average, to 4,232 hours, however, the workload of the discipline represents just over 1% of the total offered. Less than half of the courses, 43%, approach the discipline in a theoretical-practical way, with the remainder being only theoretical. Conclusion: The presence of the discipline of orofacial pain and temporomandibular disorders in Dentistry courses in Northeast Brazil is still low. Due to their relevance, measures must be planned so that their inclusion is prioritized.